Peningkatan Hasil Belajar Menulis Cerpen Melalui Metode Song Lyrics Peserta Didik Kelas XI MIPA 3 TP 2021/2022 di MAN 2 Banjarnegara - Sutiyani Sutiyani (Madaris: Jurnal Guru Inovatif, 2023)
Distance or online learning makes students close to digital and virtual worlds including songs. Learning to write short stories is difficult. The purpose of this study was to improve the learning outcomes of writing short stories for students in class XI MIPA 3 TP 2021/2022 at MAN 2 Banjarnegara through the Song Lyrics Method. Based on initial data, learning outcomes are low. It was obtained data from 35 students with a very poor rating of 5.7%, 34.3% lacking, 37.1% sufficient, 22.9% good, and 0% very good with the highest score 88, lowest 56, average 74 , and completeness only reached 60%. For this reason, an appropriate learning method is needed. To overcome this problem the authors conducted a class action research using the Song Lyrics Method. The procedures carried out include planning, action, observation, and reflection. This research was carried out from June 1 to December 2021. The data obtained from the learning outcomes were analyzed using a comparative descriptive system between the initial state and the results of the inter-cycle actions. Based on the analysis and reflection of the learning process, significant final results were obtained from cycle 1 to 2. There was an increase of 17.1% of students with very good and good predicates and a decrease of 22.9% with sufficient predicate, 20% with less predicate and an increase in the highest score 5.7%, the lowest is 28.6%, the average is 20%, and the completeness is 14% Abstrak Pembelajaran jarak jauh atau on line membuat peserta didik dekat dengan digital dan dunia maya termasuk di dalamnya lagu. Pembelajaran menulis cerpen sukar.  Tujuan penelitian ini untuk meningkatkan hasil belajar menulis cerpen peserta didik kelas XI MIPA 3 TP 2021/2022 di MAN 2 Banjarnegara melalui Metode Song Lyrics. Berdasarkan data awal hasil belajar rendah. Hal itu diperoleh data  dari 35 peserta didik berpredikat sangat kurang 5,7%  , kurang 34,3%, cukup 37,1%, baik 22,9%, dan sangat baik 0% dengan nilai tertinggi 88, terendah 56, rata-rata74, serta ketuntasan baru mencapai 60%. Untuk itu diperlukan metode pembelajaran yang tepat. Untuk mengatasi masalah tersebut penulis melakukan penelitian tindakan kelas menggunakan Metode Song Lyrics. Adapun prosedur yang dilakukan meliputi perencanaan, tindakan, observasi, dan refleksi. Penelitian ini dilakukan mulai 1 Juni s.d. Desember 2021. Data yang diperoleh dari hasil belajar yang dianalisis dengan sistem deskriptif komparatif antara keadaan awal dan hasil tindakan antarsiklus. Berdasarkan analisis dan refleksi proses pembelajaran diperoleh hasil akhir yang signifikan dari siklus 1 ke 2. Hal tersebut terdapat peningkatan sebanyak 17,1% peserta didik berpredikat sangat baik dan baik dan menurunnya 22,9% berpredikat cukup, 20% berpredikat kurang serta meningkatnya nilai tertinggi 5,7%, terendah 28,6%,rata-rata 20%,dan ketuntasan 14%